DOES OVERLAP SYNDROME CONTRIBUTE TO CLINICAL DIFFERENCES IN SYSTEMIC SCLEROSIS SKIN SUBTYPES - Vasi, I.; Okyar, B.; Ersozlu, D.; Ozgur, D. S.; Bes, C.; Cefle, A.; Akdogan, A. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Descriptive Studies; Observational studies/registry